Principal’s Entrepreneurship Competence in Improving Teacher’s Entrepreneurial Skill in High Schools - Listiningrum, Hertining Dyah; Wisetsri, Worakamol; Boussanlegue, TCHABLE (Journal of Social Work and Science Education, 2020)
This study described the principals' entrepreneurial competencies in increasing entrepreneurship knowledge for teachers, fostering and developing an entrepreneurial spirit for teachers and helping teachers to apply entrepreneurial spirit to the learning process. This research is a qualitative descriptive study. The subject of the study is the principal and teachers. The object of the principal's entrepreneurial competency research. The data in this study were in the form of observations, documentation, and interviews. Data analysis using interactive analysis of the Miles and Huberman model includes data collection, data reduction, data display, and conclusions. The results in this study are knowledge about technology-based entrepreneurship for teachers as a professional educator carried out through entrepreneurship socialization, providing information about technological developments, and providing motivation to develop teacher potential. Teachers have the ability to apply the spirit of entrepreneurship in the learning process so that they are able to produce students who are superior competitiveness.